Loss of institutional accreditation and its effects on first-year retention: Universidad de Las Américas 2010-2014, Chile - Castro, Cristóbal A.; Pavez, Constanza A.; Contreras, Francisco J. (Centro de Información Tecnológica, 2021)
The primary objective of the present study is to determine how much of the impact that the loss of accreditation (2013) has on first-year retention rate at the Universidad de Las Américas (Chile) is due to a worsening of financing conditions and how much is due to degradation of the perception about the institution’s quality. Using administrative data from the Universidad de Las Américas between the years 2010 and 2014, a non-linear decomposition econometric analysis technique for discrete models is applied. The results show that retention rate drop is mainly due to the loss of access to governmental financing credits, although changes in perception explain up to a third of retention rate drop. By comparing the 2013 and 2014 cohorts, it is concluded that perceptions most affect the educational institution in the year (2013) that accreditation is lost.
Pérdida de acreditación institucional y sus efectos sobre la retención de primer año: Universidad de Las Américas 2010-2014, Chile
Keywords: Higher education; Retention; Funding; Accreditation